The Effectiveness of Green Advertising: Influences of Claim Specificity, Product's Environmental Relevance and Consumers' Pro-environmental Orientation - Umit Alniacik; Cengiz Yilmaz (Amfiteatru Economic Journal, 2012)
This study investigates the influences of claim specificity, the product's environmental relevance, and the respondents' proenvironmental orientation on the effectiveness of green advertising among Turkish consumers. An experimental study is conducted using hypothetical print advertisements for two product categories (laundry machines as a high relevance product; DVD player as a low relevance product). Findings indicate that the specificity of the green claim does not exert a significant effect on consumer evaluations towards high relevance product advertisement, while specific green claims significantly improve the communication effectiveness of the low environmental relevance product advertisement. The theoretical and managerial implications of these findings are discussed.
Keywords: M37; M31; Q56; 330; advertisement effectiveness; claim specificity; experimental design; green advertising; product environmental relevance